(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
In contemporary healthcare settings, collaboration between social workers and nurses plays a pivotal role in delivering comprehensive and holistic care to patients. With the advancement of technology, new opportunities arise to enhance this collaboration and improve patient outcomes. This article explores the multifaceted ways in which technology facilitates collaboration between social workers and nurses.